Efektivitas Metode Jarimatika Dalam Meningkatkan Kemampuan Berhitung Penjumlahan Bilangan Asli Sampai 50 Bagi Anak Cerebral Palsy (Single Subject Research Kelas II/D di SLBN Serdang Bedagai) - Whiend Indani Putri Agacha; Asep Ahmad Sopandi (Jurnal Penelitian Pendidikan Khusus, 2023)
The problem that researchers at the State Special School of Serdang Bedagai have in class II cerebral palsy children who are unable to add natural numbers up to 50 is the driving force in this study. To overcome this problem and improve numeracy skills, the researcher offers a solution in the form of the Jarimatika method. In this study, an experimental approach was used in the form of Single Subject Research (SSR) with an A-B-A design. In the intervention that was completed for six meetings, the child's ability increased at this meeting. In the baseline phase A2 which was completed in four meetings, after the intervention or the finger treatment treatment, it was seen that the child's ability increased. The results of this study indicate that children with cerebral palsy grade II at SLB Negeri Serdang Bedagai can add up natural numbers up to 50 using the Jarimatika method. The results showed that the numerical ability of the children with cerebral palsy was influenced by the Jarimatika method, this was seen based on the results of observations and the results of the children's numeracy test in the baseline-A1 phase, intervention, and baseline-A2 phase which had been studied both within and between conditions. . The development of numeracy skills can be observed by the change in the mean level which states that after using the Jarimatika method there is an increase in the mean level at each stage. This shows that the use of the Jarimatika method has proven to be effective in increasing the ability to count the addition of natural numbers up to 50 in children with cerebral palsy.Â